Leiomyosarcoma of the scalp and lower leg skin. Clinical cases and literature review - E. M. Nepomnyashchaya; Yu. V. Ulianova; M. A. Engibaryan; T. O. Lapteva; M. A. Kuznetsova (Южно-Российский онкологический журнал, 2022)
Malignant soft tissue tumors localized in the skin, particularly leiomyosarcoma, are rare. Cutaneous leiomyosarcomas could have superficial and deep forms, while subcutaneous leiomyosarcomas are usually nodular. The tumor can spread to the underlying muscle fascia. The immunophenotype of leiomyosarcoma is determined by the following antibodies: ASMA, desmin, and N-caldeston; expression of PanCK is also possible. Researchers do not have any common opinion on the clinical course and biological behavior of cutaneous leiomyosarcomas. This is probably due to the tumor heterogeneity and the carcinogenesis specificity associated with molecular genetic changes. We detected these tumors at the histological examination which resulted in an analysis of the literature and our own material. We analyzed cutaneous tumors diagnosed in 2522 patients during 5 years (2016–2020). Squamous cell and basal cell histotypes were the most common ones. We did not diagnosed cutaneous leiomyosarcoma in our material during this period. This article presents two cases of cutaneous leiomyosarcoma localized in the scalp and calf skin. Morphological and immunohistochemical profiles of the tumors are described. The immunohistochemical analysis confirmed the morphological diagnosis and established the tumor immunophenotypes. The morphological diagnosis in one case was complicated due to the rarity of this pathology and the ambiguity of the interpretation of histological changes. Analysis of histological preparations and immunohistochemical study allowed verification of the tumor as leiomyosarcoma with its characteristic immunophenotype. All of the above demonstrate the need to perform morphological and immunohistochemical tests in specialized research cancer centers.